Increased methylglyoxal formation in plasma and tissues during a glucose tolerance test is derived from exogenous glucose - Zhang, Xiaodi; Scheijen, Jean L.J.M.; Stehouwer, Coen D.A.; Wouters, Kristiaan; Schalkwijk, Casper G. (Clinical science (1979), 2023)
The dicarbonyl compound methylglyoxal (MGO) is a major precursor in the formation of advanced glycation endproducts (AGEs). MGO and AGEs are increased in subjects with diabetes and are associated with fatal and nonfatal cardiovascular disease. Previously, we have shown that plasma MGO concentrations rapidly increase in the postprandial phase, with a higher increase in individuals with type 2 diabetes. In current study, we investigated whether postprandial MGO formation in plasma and tissues originates from exogenous glucose and whether the increased plasma MGO concentration leads to a fast formation of MGO-derived AGEs. We performed a stable isotope-labelled oral glucose tolerance test (OGTT) in 12 healthy males with universally labelled D(+)13C glucose. Analysis of plasma-labelled 13C3 MGO and glucose levels at 11 time-points during the OGTT revealed that the newly formed MGO during OGTT is completely derived from exogenous glucose. Moreover, a fast formation of protein-bound MGO-derived AGEs during the OGTT was observed. In accordance, ex-vivo incubation of MGO with plasma or albumin showed a rapid decrease in MGO and a fast increase in MGO-derived AGEs. In an intraperitoneal glucose tolerance test in C57BL/6J mice, we confirmed that the formation of postprandial MGO is derived from exogenous glucose in plasma and also showed in tissues that MGO is increased and this is also from exogenous glucose. Collectively, increased formation of MGO during a glucose tolerance test arises from exogenous glucose both in plasma and in tissues, and this leads to a fast formation of MGO-derived AGEs.